Pengaruh Dukungan Sosial terhadap Resiliensi Remaja Putus Sekolah di Kota Makassar - Muhammad Aditya Pratama; Muh. Nur Hidayat Nurdin; Nur Akmal; Eva Meizara Puspita Dewi (Flourishing Journal, 2023)
Resilience is important for out-of-school adolescents so that they can make them able to bounce back from the problems faced after dropping out of school. One factor that can increase the resilience ability of out-of-school adolescents is social support. This study aimed to determine the effect of social support on the resilience of out-of-school adolescents. The sampling technique in this study used Snowball Sampling with a total of 228 subjects. The measuring instrument used is the Social Support Scale, with a reliability value of 0.827. The resilience Scale was used to measure the level of resilience in this study with a reliability value of measuring instruments of 0.928. This study used a simple linear regression analysis technique, which showed the study results that there was an effect of social support on resilience with a significance value of 0.000 (p < 0.05). The impact of the independent variable on the variable is tied to the value of R = 0.490, which shows a positive value, and, the results of R Square in this study are R2 = 0.240, which means that social support has an influence of 24% on resilience with weak categories. AbstrakPentingnya kemampuan resiliensi dipunyai oleh remaja putus sekolah sehingga mampu membuat remaja putus sekolah dapat bangkit kembali dari permasalahan yang dihadapi pasca putus sekolah. Salah satu faktor yang mampu meningkatkan kemampuan resiliensi remaja putus sekolah ialah dukungan sosial. Kajian ini bertujuan untuk melihat dampak dukungan sosial pada resiliensi remaja putus sekolah. Metode penghimpunan sampel pada kajiaan ini menerapkan teknik Snowball Sampling pada jumlah subjek yakni 228 orang. Alat ukur yang digunakan adalah Social Support Scale dalam mengukur dukungan sosial dengan nilai reliabilitas alat ukur yakni 0,827. Skala Resiliensi untuk mengukur tingkat resiliensi dalam penelitian ini dengan nilai reliabilitas alat ukur sebesar 0,928. Kajian ini menerapkan metode analisa regresi linear sederhana yang menunjukkan hasil kajian pada dampak dukungan sosial pada resiliensi dengan nilai signifikansi sebesar 0,000 (p < 0,05). Dampak variabel bebas pada variabel terikat pada nilai R= 0,490 yang menunjukkan nilai positif serta, hasil R Square dalam penelitian ini sebesar R2 = 0, 240 yang artinya dukungan sosial memiiki dampak yakni 24% terhadap resiliensi dengan kategori lemah.